The influence of ethanol fractions of infusa of Plantago major L. leaves in effectivity of octyl methoxycinnamate as active ingredient of sunscreen - Nining Sugihartini; Marchaban .; Suwidjiyo Pramono. (Indonesian Journal of Pharmacy, 2005)
Octyl methoxycinnamate is an active ingredient of that is degraded by solar irradiation resulting it usage as sunscreen becomes less effective. An antioxidant has capability as a photo-protector. Flavonoid in the ethanolic fraction of Plantago major, L. leaves is reported to have an antioxidant. This research was aimed to examine the influence of the addition of the ethanolic fraction of Plantago major, L. leaves to the effectiveness of octyl methoxycinnamate as a sunscreen. In this research, two formulas were prepared. Formula I contained octyl methoxycinnamate per se and formula II contained a mixture (1:1) of octyl methoxycinnamate and ethanolic fraction of Plantago major, L. leaves. Both formulas were exposed to the sun light for 5 hours (09.00-14.00 WIB) in which samples were taken every hour. The effectiveness of octyl methoxycinnamate was calculated based on the percentage of erythema transmission and the percentage of pigmentation transmission, prior and after the irradiation by the sun light for 5 hours. The statistical data analysis was performed based on the Student t test with a confidence level of 95%. The addition of the ethanol fraction of Plantago major, L. leaves significantly reduced the percentage of the erythema transmission after solar irradiation (p